Tide Analysis from Bathymetric Soundings: A Method for Extracting Tidal Amplitude and Phase Errors from Overlapping Soundings - Osborne, Alex (The International Hydrographic Review, 2010)
This paper describes a method for identifying phase and amplitude tide errors in bathymetric soundings. It is applicable to bathymetric surveys where tide is measured and then used to reduce raw soundings to datum (as opposed to absolute depth measured using kinematic GPS). The problem of tide inaccuracy is briefly explained, along with a description of some of the key concepts which should be understood. The processing method is then explained and demonstrated using a real-world example. The optimum tide curve for this example dataset is identified based on analysis of the soundings.